Konsentrasi dan Kebugaran Meningkatkan Produktivitas Kerja - Ivo Kristina Dalimunthe; Fransisca Chondro (Fakultas Kedokteran Universitas Trisakti, 2022)
Background Work productivity is important for a company to maximise company performance. Work productivity can be affected by concentration and physical fitness. Concentration is the ability to focus attention on work. Meanwhile, physical fitness is the ability of the body to perform activities without exhaustion. This study was conducted to determine the value of the relationship between concentration, fitness and employees' work productivity. MethodsThis study used a cross-sectional design. The subjects were employees of Cooperative Service Bandung, and the subject selection used non-probability sampling. Army Alpha Test measured concentration. A non-exercise fitness test assessed the level of physical fitness. Work productivity was assessed using a work productivity questionnaire. Data analysis was performed using SPSS version 20 with univariate analysis and bivariate Chi-square test. A total of 130 respondents participated in this study. ResultsThe Chi-square test results showed a significant relationship between concentration level and work productivity (p=0.001) and a relationship between the level of fitness and work productivity (p=0.031). ConclusionsThus concentration and physical fitness lead to work productivity.